La descripción de las imágenes en Internet a través del análisis de 30 bancos de imágenes - Doucet, Anne-vinciane (Revista General de Información y Documentación, 2009)
This article analyses the description of 30 environmental image banks on the Internet. After a short definition of the image banks, documental representation, image retrieval and metadata (EXIF and IPTC), I will analyze various factors to determine the existence (or non-existence) of normalization in caption image: the global profile of image banks and the components of image details, as well in its terminology as in the frequency of use of these components.Furthermore, I will analyze the caption has a label in the image detail or not, and its size (words, phrases, paragraphs), the frequency of use of metadata and finally, I will present documental tools and retrieval presentation.This analysis allows us to conclude there is a large variety of documental description of images on the Internet.